(untitled) (Research, Society and Development, 2022)
The aim of the present study was to evaluate mortality and changes in laboratory parameters in the presence of positive cultures for bacteria and fungi in COVID-19 patients admitted to ICUs, in a tertiary teaching hospital in Mato Grosso do Sul. This is a retrospective observational study carried out by collecting clinical and laboratory data from adult patients admitted to ICUs, with a confirmed diagnosis of SARS-CoV-2, between the months of July and August, 2020. The presence of at least one positive culture in critically ill patients with COVID-19 was associated with higher mortality rates, longer hospital stays, and higher levels of D-dimer and C-reactive protein. Male patients were more likely to have positive cultures, and older age was associated with lower platelet counts. Higher white blood cell counts and lower platelet counts were also associated with higher mortality rates. The cultures that showed the highest positivity rate were the tracheal aspirate cultures. The main microorganisms found in the culture tests were the yeast Candida albicans and the coagulase-negative Staphylococcus species. The bacteria Acinetobacter baumannii and Klebsiella pneumoniae stood out for presenting more frequent resistance profiles. Therefore, it is important to adopt measures to prevent secondary hospital infections in patients with COVID-19 and the development of resistance mechanisms by microorganisms of clinical relevance. The laboratory stands out in the identification of these microorganisms and in directing the use of the most appropriate antibiotics and antifungals for each specific case.